Donor performance of combat readiness skills of special forces soldiers are maintained immediately after whole blood donation. Issue 3 (28th June 2012) - Strandenes, Geir; Skogrand, Håkon; Spinella, Philip C.; Hervig, Tor; Rein, Erling B.
<x xml:space="preserve">Abstract</x> BACKGROUND: Bleeding is a major cause of death in combat settings, and combat casualties in shock may benefit from fresh whole blood (FWB) transfusion. "Buddy transfusion" is a well‐known lifesaving intervention, but little is known about donor combat safety aspects immediately after blood donation. The objectives of this study were to explore the effects of donation of 1 unit of blood on physical and combat‐related performance among active duty soldiers. We also investigated the feasibility of a short training program to teach nonmedics buddy transfusion. STUDY DESIGN AND METHODS: Twenty‐five fit male soldiers from a special forces unit were divided into three groups and tested on 1) a Bruce protocol treadmill stress test, push‐ups, and pull‐ups; 2) a 50‐round rapid pistol shooting test; and 3) an uphill hiking exercise carrying a 20‐kg backpack. After baseline testing, the soldiers performed the tests again (2‐6 min) after donating 450 mL of blood. The training program included blood collection and reinfusion procedures and we measured success rate of venipuncture, time for blood collection, and success in placing sternal intraosseous needle and reinfusing 1 unit of autologous blood. RESULTS: We did not find any significant decrease in performance either in physical or in shooting performance after donating blood. Nonmedic soldiers had a 100% success rate in blood collection and also infusion on fellow soldiers after a short introduction to the procedures. CONCLUSION: This study supports the fact that buddy transfusion may be feasible for healthy well‐trained soldiers and does not decrease donor combat performance under ideal circumstances.